CONDIÇÃO DE SAÚDE, FUNCIONALIDADE E RISCO DE QUEDAS EM IDOSAS RESIDENTES EM COMUNIDADE - Luiza Araújo Cerqueira, Maria; Menezes Lima, Caroline; das Mercês Rodrigues , Thailan; Henrique Fernandes, Marcos; Schettino Ribeiro de Paula, Ludmila; Matos de Araújo, Cláudineia (Semana Baiana de Fisioterapia, 2026)